MANAJEMEN TENAGA PENDIDIK DI PONDOK PESANTREN SALAFIYAH IQRO PALANGKA RAYA - Khusnul Hasanah; Triwid Syafarotun Najjah; Slamet Riyadi (Jurnal Kepemimpinan dan Pengurusan Sekolah, 2026)
This study aims to describe the management of teaching staff at the Salafiyah Iqro Islamic Boarding School in Palangka Raya, which includes planning, recruitment, placement, training, rewards, and termination of teaching staff. This study uses a qualitative approach with a descriptive research type. Data collection techniques were conducted through interviews, and observation, while data analysis used data reduction, data presentation, and conclusion drawing techniques. The results show that teacher management at the Salafiyah Iqro Islamic Boarding School in Palangka Raya is carried out in a simple and familial manner, but still reflects the functions of educational management. Teacher planning is carried out in a simple manner by adjusting to the needs and characteristics of the boarding school. Teacher recruitment is carried out internally through recommendations from the boarding school environment without open announcements. The placement of teaching staff is adjusted to their competence, educational background, and the subjects they teach. The development of teaching staff has not been carried out formally and structurally, but is carried out through guidance from leaders, deliberations, and comparative study activities. Rewards are given in material and non-material forms, while the dismissal of teaching staff is not carried out formally.